The role of tenure security in farmers' decision-making on investment in improved seeds: insights from mental models - Murken, Lisa; Krähnert, Kati; Van den Broek, Karlijn; Adriko, John; Gornott, Christoph (Ruhr economic papers, 2024)
This paper applies a mental model approach to study the role of tenure security in farmers’ decisionmaking on agricultural investment in Uganda. We investigate the role that both perceived tenure security and formal land rights, measured by the possession of land certificates, play. Our focus is on investment in improved seeds, a widely applied strategy in agricultural development and climate change adaptation. The study design leverages the roll-out of a large land demarcation and registration project, which creates exogenous variation in farmers’ tenure security. Results show that, in contrast to expectations derived from economic theory, tenure security plays only a minor role in farmers’ decision-making process to invest in improved seeds. Out of 15 potential factors determining a farmer’s investment decision, both perceived tenure security and possession of a land certificate are among the least chosen factors, regardless of whether or not households participated in the land registration project. A heterogeneity analysis reveals that female-headed households value formalized land rights more than male-headed households.